2015
DOI: 10.1016/j.rsma.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of the microplankton community along a tropical estuary

Abstract: Microplankton organisms are an important link in the transfer of matter and energy between the benthic-pelagic microbial food web and higher trophic levels in estuaries. Although tropical estuaries are among the most productive aquatic systems globally, information on the spatial and seasonal dynamics of microplankton in such systems is scarce. In order to identify which variables control microplankton abundance and community structure a number of environmental variables were measured along the tropical Gulf o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 81 publications
3
23
0
Order By: Relevance
“…The flow of the Tempisque River affects phytoplankton abundance, community structure, and primary production in the inner basin of the Gulf of Nicoya due to its effects on water column stability, nutrient concentration, and light availability. Fresh water flow changes seasonally and controls the stability of the water column (Voorhis et al 1983;Seguro et al 2015). During the dry season, tidal and residual currents mix the water column between Sta.…”
Section: Discussionmentioning
confidence: 99%
“…The flow of the Tempisque River affects phytoplankton abundance, community structure, and primary production in the inner basin of the Gulf of Nicoya due to its effects on water column stability, nutrient concentration, and light availability. Fresh water flow changes seasonally and controls the stability of the water column (Voorhis et al 1983;Seguro et al 2015). During the dry season, tidal and residual currents mix the water column between Sta.…”
Section: Discussionmentioning
confidence: 99%
“…Based on that, the nitrogen was shown to be a limiting factor for the diatoms blooms and the phosphorus was a limiting factor for the proliferation of green algae and euglenoids. According to SIN et al (2015) and SEGURO et al (2015) it is common the nitrogen being the main limiting factor for marine phytoplankton and the phosphorus for continental phytoplankton. According to RODRIGUES and CUTRIM (2010), phosphorus is usually the main nutrient for microphytoplankton in the estuaries of Maranhão, suggesting that this community is physiologically well adapted to the conditions of nutrients mixing.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the microphytoplankton composition, diatoms were the most representative group, followed by dinoflagellates (SEGURO et al, 2015), which are transported by tidal currents, and are more frequent in the dry season (PAIVA et al, 2006). The dominance of diatoms is common in estuarine systems due to their euryhaline nature (SENA et al, 2015) and it is correlated directly with the silicate content, since the major source of silica is from the continent and the diatoms frustules have silica in their composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this assumption can be invalid in the dynamic coastal environments. Recent studies have shown that entrainment and upwelling processes (mixing with O 2depleted subsurface water) can lead to significant underestimation in NCP MLD using the O 2 /Ar method, especially in coastal upwelling zones (Castro-Morales et al, 2013;Nicholson et al, 2012;Shadwick et al, 2015;Teeter et al, 2018). As most regions in our study were characterized by the persistent surface stratification (Figs.…”
Section: Comparison Of Ncp Estimationsmentioning
confidence: 60%